PERSEPSI PENGUNJUNG PADA MUSEUM SEBAGAI TEMPAT TUJUAN WISATA DAN MEDIA PENDIDIKAN NON-FORMAL UNTUK MENINGKATKAN APRESIASI NILAI-NILAI KEJUANGAN - Jazuli Ahmad (Jurnal Riset Manajemen Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha Program Magister Manajemen, 2015)
This research is motivated by the significant difference between the museum visitor in Yogyakarta. The purpose of this study is to determine whether any differences in the perception of visitors of the museum as a tourist destination, the media of non-formal education as an object to increase the appreciation to historical values. The population in this study are all visitors who comes to the museum in Yogyakarta. Total of samples are 120 respondents and using purposive sampling method. Purposive sampling included in non-probability sampling techniques.Based on statistical data analysis, the statement in this research is valid and reliable because that is consistent and reliable fixed anytime and by anyone who will conduct research in a similar context. While the Chi quare test showed no visitors who have different perceptions and there is a visitor who does not have different perceptions of the factors that affect visitors to the museum in Yogyakarta. This can be seen from the results of the P value (Asymp. Sig.)> 0.05 and P value (Asymp. Sig.) <0.05. And for crosstab test results also showed no variables are interrelated and there is a variable that does not have a relationship because there is a calculated value of > table and calculate the < table.To maintain and increase the number of visitor, museum management should strive to improve and enhance the indicators that have value Asymp Sig. > 0.05 so that the perception of the museum’s visitors better than before. Meanwhile, in order to compete in the competitive business engaged in the service, the museum should improve the relationship between the variables and the other variables especially those with a low count .